ANALISIS TRANSFORMASI STRUKTURAL PEREKONOMIAN ACEH - Dedi Sufriadi (JURNAL EKOMBIS, 2018)
The main aims of this observation are 1.to figure out the transformation of structural economy in Aceh; and 2. To analyze the economical sectors which are available to be developed in Aceh. This research was analyzed using Classic Shift Share Analysis, Esteban-Marquillas Shift Share Analysis and Location Quotient (LQ). The results based on the Shift Share Analysis shows that years of 2008-2012 there have been changes in the economic structure of Aceh primary sector to tertier sector and secondary sector. where as years of 2000-2004 and years of 2004-2008 haven‘ t been changes in the economic structure of Aceh. The economic structural transformation during analysis years in 2008-2012 happened because the contribution from primary sector which is decreasing with  the low relative growth,  but at the same time the constribution of the tertier sector is increasing with the high relative growth as well as secondary sector. Agriculture sector, mining and quarrying sector and services sector are the basis sectors and can be seeded to be developed on the economy Aceh. It’s expected that the governments, especially in Aceh to pay attention and to develop the economical sectors in Aceh. This can be done by issuing policies that potential for the development of economic sectors and also formulate policies to begin to develop the leading sectors with a focus on sectors which have the advantages as well as synergize with other potesial sector in order to produce a multiplier effect on the communities increased revenue and the acceleration of economic development and multiply again the sectors that potential still to be developed so that the future is expected to be a potentially valuable sector.Keywords: The economic structural transformastion, Specialization, Competitive advantage, Location quotient (LQ)